Decision-making tool for mitigation of the coastal erosion and extreme wave impacts in the coastal zone, in the context of climate change - Liaros, S; Poulos, S.E.; Kampanis, N.; Alexopoulos, J.D.; Alexandrakis, G.; Karditsa, A.; Ghionis, G.; Vassilakis, Emm; M. Hatzaki; Nastos, P.; Nomikou, P.; Kotinas, V.; et al. (2nd International Scientific Conference on Design and Management of Port Coastal and Offshore Works, 2023)
The tool assesses natural factors and the impact of human activities as well as the available mitigation measures in a cost-benefit perspective and with a view to mitigating the impacts of climate change. Therefore, the tool is designed to respond to both erosion (as a natural disaster) and erosion due to human (inappropriate) intervention, as well as CM&D (eg, sea level rise, extreme wave events). The innovation of the project is based on the creation of a multi-parameter decision making tool (ILIDA_KIT) related to climate change mitigation and resilience to coastal erosion and extreme wave events in the context of integrated coastal zone management. ILIDA_KIT relies on a multi-disciplinary interactive platform in a GIS environment that through the development of a set of appropriate indicators (environmental, anthropogeographic, economic) can be parameterised. The ultimate purpose of the tool is to select the most appropriate intervention (intensity, size, time horizon) measure, based on the costbenefit analysis, considering both the protection and the sustainable development of the coastal zone.